The IoT-Based ECG Monitoring Minimum System Design - Farhan Ghifari, Ahmad
One of the way to show the heart abnormality is by reading an electrocardiogram (ECG) signal. The study of developing IoT-based ECG monitoring system on mobile application is growing. One of the study of IoT-based ECG monitoring was carried out by Chhabra and Kalsi (2017). But it still has limits, the system requires a good internet connection to be able to find out the condition of the heart based on the electrocardiogram signal that is read. In addition, the system uses a Raspberry Pi that has a complex system with a relatively more expensive price. In this research a minimum system of Internet of Things (IoT) based electrocardiogram monitoring was designed. The system allows users to monitor without internet for short distances which is less than 100 meters using bluetooth media. This electrocardiogram minimum system was built using Atmega328P as IC on microcontroller and AD8232 as ECG reader. During monitoring, users can connect to doctor's smartphone which is located at a distance of more than 100 meters using the internet. When the patient’s still using the system, the signal is automatically stored on the patient’s smartphone so that the signal data can be accessed again and sent anytime to the doctor. The total cost needed for this minimum system of electrocardiogram monitoring is only 28.65% of the cost of the system built by Chhabra and Kalsi (2017). Thus the purpose of this research is fulfilled, namely to build an IoT device that can be used to monitor electrocardiogram signals by doctors from a distance.